Hearing the voices of Australian healthcare workers during the COVID-19 pandemic. Issue 1 (17th December 2020) - Ananda-Rajah, Michelle; Veness, Benjamin; Berkovic, Danielle; Parker, Catriona; Kelly, Greg; Ayton, Darshini
Abstract : Background: The statistics of healthcare worker (HCW) COVID-19 infections do not convey the lived experience of HCWs during the pandemic. This study explores the working conditions and issues faced by Australian HCWs. Methods: Qualitative analysis of free-text responses from Australian HCWs from 3 August to 26 October 2020 from an open letter calling for better respiratory protection for HCWs, transparent reporting of HCW COVID-19 infections and diversity in national infection control policy development. The open letter was sent to an email list of 23 000 HCWs from a previous campaign and promoted on social media. Results: Among 3587 HCWs who signed the open letter during the study period, 569 free-text responses were analysed. Doctors and nurses accounted for 58% and 33% of respondents, respectively. Most respondents came from Victoria (48%), New South Wales (20%), Queensland (12%) or Western Australia (11%). Dominant themes included concerns about: work health and safety standards; guidelines on respiratory protection including the omission of fit-testing of P2/N95 respirators; deficiencies in the availability, quality, appropriateness and training of personal protective equipment; and a command-and-control culture that enabled bullying in response to concerns about safety that culminated a loss of trust in leadership, self-reported COVID-19 infections in some respondents and moral injury. Conclusion: Deficiencies in work health and safety, respiratory protection, personal protective equipment and workplace culture have resulted in a loss of psychological and physical safety at work associated with an occupational moral injury. The challenge for healthcare leaders is to repair trust by addressing HCW concerns and fast track solutions in collaboration with them.